OCCURRENCE OF SPEECH ACTIVITY IN INTERNET DISCOURSE - Turakulova Nigora Eminovna; Azamova Dilafruz Bakhodirova (Galaxy International Interdisciplinary Research Journal, 2023)
This article shows that the appropriateness of communicative and informative content ensures the integrity of the macro unit of the communication system. It is also revealed that the conversational speech on the Internet and social networks brings new concepts more and more.